PERBANDINGAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN E-LEARNING GOOGLE CLASSROOM DI KELAS VII SMP NEGERI 7 PEMATANGSIANTAR TAHUN PELAJARAN 2020/2021 - Hutagaol, Polemon; Purwanti Purba, Devie (Jurnal Metabio, 2021)
This study aims to determine the differences in student learning outcomes and the magnitude of the differences in student learning outcomes using the Google Classroom E-Learning learning model on environmental pollution in seventh-grade students at SMP Negeri 7 Pematangsiantar in the 2020/2021 academic year. The population was 288 students, consisting of 9 classes, and the sample was taken using Cluster Random Sampling, resulting in two classes: experimental class I (VII-1) with 32 students and experimental class II (VII-2) with 32 students. Experimental class I was treated using the Google Classroom E-Learning learning model, while experimental class II was treated using the offline learning model. Data analysis was performed using SPSS 21 to determine the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The results obtained an average post-test score of 87.66 for experimental class I and 85.16 for experimental class II, with a difference in learning outcomes of 2.5. From the results of the hypothesis testing (t-test), the calculated t (2.625) > t table (1.99) at a significance level of α = 0.05 and degrees of freedom (df) = 62, therefore, Ho is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the Google Classroom E-Learning and Offline learning models on environmental pollution material for class VII of SMP Negeri 7 Pematangsiantar in the 2020/2021 Academic Year. It is concluded that there is a difference in student learning outcomes using the Google Classroom E-Learning and Offline learning models on environmental pollution material in class VII of SMP Negeri 7 Pematangsiantar in the 2020/2021 Academic Year.